1986
DOI: 10.1111/j.1464-410x.1986.tb09094.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Consequences of Forced Diuresis Following Prostatectomy

Abstract: The efficacy and metabolic consequences of a standardised forced diuresis regime following prostatectomy were studied in three parts. A retrospective review of 372 patients. A detailed prospective study of blood and urine electrolyte changes in 25 patients. A prospective study of urinary oxalate levels in 15 patients. The regime was effective in safely preventing post-operative clot retention. In 54% of patients the plasma sodium fell below 135 mmol/l. Hypokalaemia was mild and transient except in patients on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…Chassard et al (8) observed that 40 and 60 min after 875, 1,475, and 2,075 mL of 1.5% glycine were intravenously infused in pigs, the ionized calcium level significantly decreased. Malone et al (9) found that among patients undergoing transurethral prostatectomy using glycine, those with fall of more than 10 mM/L sodium also had a decreased serum calcium level. However, hypocalcemia can result from the complexes of calcium and oxalic acid, another metabolic product of glycine (10).…”
Section: Discussionmentioning
confidence: 99%
“…Chassard et al (8) observed that 40 and 60 min after 875, 1,475, and 2,075 mL of 1.5% glycine were intravenously infused in pigs, the ionized calcium level significantly decreased. Malone et al (9) found that among patients undergoing transurethral prostatectomy using glycine, those with fall of more than 10 mM/L sodium also had a decreased serum calcium level. However, hypocalcemia can result from the complexes of calcium and oxalic acid, another metabolic product of glycine (10).…”
Section: Discussionmentioning
confidence: 99%
“…Malone et al [7] also found patients with hyperoxaluria after TURP, but there was no correlation between hyper oxaluria and hyponatraemia. Another observation casting doubt on the hazards of calcium oxalate stone formation due to glycine absorption was that the oxalate excretion was normal during the postoperative follow-up in 2 pa tients who developed a severe transurethral resection syn drome [7,8], In the present study, 22 g of glycine was administered by intravenous infusion to mimic the absorption of 1,500 ml of 1.5% glycine solution during TURP. The results show that glycine did not significantly change the baseline urinary excretion rate of oxalate.…”
Section: Discussionmentioning
confidence: 96%
“…Potassium excretion is even known to increase transiently in connec tion with TURP [7] and after administration of glycine solution to elderly men not undergoing surgery [12].…”
Section: Discussionmentioning
confidence: 99%
“…Also the rise in serum concentration of solutes gained from the absorbed fluid such as glucose, glycine and sorbitol [19] or metabolites presumed to originate from them such as ammonia [27] and oxalates [45] have been incriminated as possible pathogenesis for the TURP syndrome. In the present series, however, neither hypoalbuminaemia, hypocalcaemia nor hyperkalaemia were significant in the pathogenesis of the syndrome.…”
Section: Discussionmentioning
confidence: 99%